Neoadjuvant radiotherapy for locally advanced and high‐risk breast cancer. Issue 3 (5th April 2021) - Chidley, Phoebe; Foroudi, Farshad; Tacey, Mark; Khor, Richard; Yeh, Janice; Bevington, Elaine; Hyett, Anthony; Loh, Su Wen; Chew, Grace; McCracken, James; Neoh, Derek; Yeo, Belinda; et al.
Abstract: Introduction: Neoadjuvant radiotherapy (NART) as part of a multi‐modality approach for locally advanced breast cancer (LABC) requires further investigation. Importantly, this approach may allow for a single‐staged surgical procedure, with mastectomy and immediate autologous reconstruction. Multiple other potential benefits of NART include improved pathological downstaging of breast disease, reduced overall treatment time, elimination of time period with breast tissue deficit and improved patient satisfaction. Methods: This is a retrospective multi‐institutional review of patients with LABC and high‐risk breast disease undergoing NART. Eligible patients sequentially underwent neoadjuvant chemotherapy (NACT) with or without HER2‐targeted therapy, NART, followed by mastectomy with immediate autologous breast reconstruction (BR) 4‐ to 6 weeks post‐completion of radiotherapy. Patient and tumour characteristics were analysed using descriptive statistics. Surgical complications were assessed using the Clavien–Dindo Classification ( Ann Surg 2004; 240 : 205). Results: From 3/2013 to 9/2019, 153 patients were treated with NART. The median age was 47 years (IQR 42–52), with median body mass index of 27. Eighteen patients experienced Grade 3 acute surgical complications. This included 13 Grade 3B breast‐site events and 9 Grade 3B donor‐site events, where further surgical intervention was required for management of wound infection, wound dehiscence, flap or mastectomy skin necrosis, haematoma and internal mammary venous anastomotic thrombosis. No autologous flap loss was observed. Conclusion: Neoadjuvant radiotherapy facilitates a single‐stage surgical procedure with mastectomy and immediate autologous BR, eliminating the delay to reconstructive surgery and thus shortening a woman's breast cancer journey. The findings of this review support the use of NART, with comparable rates of surgical complications to standard sequencing.